2020
DOI: 10.3390/md18060316
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of a Fucose-Rich Fucoidan Isolated from Saccharina japonica against Ultraviolet B-Induced Photodamage In Vitro in Human Keratinocytes and In Vivo in Zebrafish

Abstract: A fucose-rich fucoidan was purified from brown seaweed Saccharina japonica, of which the UVB protective effect was investigated in vitro in keratinocytes of HaCaT cells and in vivo in zebrafish. The intracellular reactive oxygen species levels and the viability of UVB-irradiated HaCaT cells were determined. The results indicate that the purified fucoidan significantly reduced the intracellular reactive oxygen species levels and improved the viability of UVB-irradiated HaCaT cells. Furthermore, the purified fuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…These results demonstrated that fucoidan could effectively protect HaCaT cells against UVB-induced cell death and possibly achieved this by scavenging intracellular ROS. Su et al have evaluated the photoprotective effect of fucoidan (LJSF4) isolated from Saccharina japonica in HaCaT cells [ 40 ]. The results indicated LJSF4 contains 56.55% carbohydrate and 30.72% sulfate contents, and it increased the viability of UVB-irradiated HaCaT cells by 16.13% at the concentration of 100 μg/mL [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results demonstrated that fucoidan could effectively protect HaCaT cells against UVB-induced cell death and possibly achieved this by scavenging intracellular ROS. Su et al have evaluated the photoprotective effect of fucoidan (LJSF4) isolated from Saccharina japonica in HaCaT cells [ 40 ]. The results indicated LJSF4 contains 56.55% carbohydrate and 30.72% sulfate contents, and it increased the viability of UVB-irradiated HaCaT cells by 16.13% at the concentration of 100 μg/mL [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Su et al have evaluated the photoprotective effect of fucoidan (LJSF4) isolated from Saccharina japonica in HaCaT cells [ 40 ]. The results indicated LJSF4 contains 56.55% carbohydrate and 30.72% sulfate contents, and it increased the viability of UVB-irradiated HaCaT cells by 16.13% at the concentration of 100 μg/mL [ 40 ]. Compared with the present results, LJSF4 possesses a slightly stronger activity than the fucoidan isolated from H. fusiforme , possibly owing to its higher sulfate content.…”
Section: Resultsmentioning
confidence: 99%
“…Fucoidans are a family of sulfated polyfucose polysaccharides extracted from brown seaweeds. These substances possess various pharmacological properties that exert antitumor, immunomodulatory, antioxidant, and anti-inflammatory effects (18,19). Previous studies have demonstrated that fucoidans also have antiphotoaging effects against UV irradiation and can be used as an ingredient in pharmaceuticals (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The photoprotective activity of fucoidan has been studied using UVB irradiated HaCaT and human foreskin fibroblast (HS 68) cells, zebrafish, and in vivo models [ 19 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ]. The earliest study on the photoprotective activity of fucoidan was carried out by Kim et al in 2008.…”
Section: Seaweed Compounds As Potential Sources Of Anti-photoagingmentioning
confidence: 99%